2009
DOI: 10.1088/0004-637x/702/1/707
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Isotope Composition of Meteorites, Earth, and Mars

Abstract: The relative abundances of calcium isotopes in the mass range 40-44 were measured in primitive and differentiated meteorites and igneous rocks from Earth and Mars in search of non-mass-dependent variations that could provide clues about early solar system processes. 40 Ca abundance found in some chondrites and all differentiated meteorites studied. It appears that isotopic heterogeneity in calcium was still present at the completion of disk formation but was homogenized during planetary accretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
163
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(186 citation statements)
references
References 81 publications
(124 reference statements)
20
163
3
Order By: Relevance
“…These results are consistent with the previous work (Jungck et al, 1984;Niederer and Papanastassiou, 1984), who also observed 48 Ca excess and no 40 Ca or 43 Ca anomalies in refractory inclusions from Allende and Leoville. In contrast, Simon et al (2009) reported up to 2 e units 40 Ca excess in two refractory inclusions from Allende, and a subsequent study reported that these two refractory inclusions also have 48 Ca excess (Moynier et al, 2010). The level of 40 Ca excess reported by Simon et al (2009) well exceeds the analytical uncertainty of e 40/44 Ca in our study, as well as those of Jungck et al (1984) and Niederer and Papanastassiou (1984).…”
Section: Nucleosynthetic Anomalies In Ca Isotopessupporting
confidence: 53%
See 2 more Smart Citations
“…These results are consistent with the previous work (Jungck et al, 1984;Niederer and Papanastassiou, 1984), who also observed 48 Ca excess and no 40 Ca or 43 Ca anomalies in refractory inclusions from Allende and Leoville. In contrast, Simon et al (2009) reported up to 2 e units 40 Ca excess in two refractory inclusions from Allende, and a subsequent study reported that these two refractory inclusions also have 48 Ca excess (Moynier et al, 2010). The level of 40 Ca excess reported by Simon et al (2009) well exceeds the analytical uncertainty of e 40/44 Ca in our study, as well as those of Jungck et al (1984) and Niederer and Papanastassiou (1984).…”
Section: Nucleosynthetic Anomalies In Ca Isotopessupporting
confidence: 53%
“…We use mass-independent Ca isotopic effects to measure the nucleosynthetic isotopic anomalies in extraterrestrial materials, such as refractory inclusions and chondrites (e.g., Simon et al, 2009;Chen et al, 2011;Lee et al, 2011). In this case, the 40 Ca/ 44 Ca, 43 Ca/ 44 Ca and 48 Ca/ 44 Ca ratios of the samples and the standard are internally normalized (indicated by N) to 42 Ca/ 44 Ca = 0.31221 (Russell et al, 1978) using an exponential law to correct for both instrumental fractionation and fractionation intrinsic to the sample.…”
Section: Group I N-group Iimentioning
confidence: 99%
See 1 more Smart Citation
“…The Moon has an isotopic composition that is identical to the silicate mantle of the Earth within the relatively tight analytical constraints provided by modern instrumentation for oxygen (Weichert et al 2001;Kohl et al 2015), silicon (Armytage et al 2012), calcium (Simon et al 2009) magnesium (Sedaghatpour et al 2013), iron (Moynier et al 2006), titanium (Zhang et al 2012), strontium (Moynier et al 2010a) and chromium (Lugmair and Shukolyukov 1998) but it has had a totally different geochemical development. The similarity in oxygen isotopes seems particularly significant as O 2-is a large anion and the packing of oxygen anions largely controls the abundance of other elements in silicates.…”
Section: The Origin Of the Moon: Current Ideasmentioning
confidence: 99%
“…As we obtain more information from Solar System materials regarding compositional or isotopic zoning, the interaction between chemistry and dynamics will be more fruitful. For example, isotopes of the refractory element Ca exhibit no variation for many differentiated bodies in the inner Solar System (75). Similarly, the volatile element N exhibits a narrow range in isotopic composition for all known planetary materials, yet this isotopic composition is distinct from the compositions of the Sun and comets (76).…”
Section: Future and Unresolvedmentioning
confidence: 99%